PRELIMINARY SURVEY ON OCCURRENCE OF APHIDS, THRIPS LEAF MINER IN TOMATO GROWING AREAS IN MOROGORO REGION TANZANIA - Materu, Christopher L; Losujaki, Essau W. (International Journal of Research -GRANTHAALAYAH, 2019)
Tomato (Lycopersicum esculentum L.) is one of the important crop in East Africa as a source of food, income and export. Occurrence of different pest including indigenous and alien in tomato fields are considered as a major threat pests to tomato growers. Worldwide pest problems in horticultural investment need to be considered carefully as their presence increase cost of production. Despite of this information in Tanzania there has been little research to update pest list infesting our tomatoes. The study was conducted in Morogoro region in Kauzeni and Bigwa wards whereby farmers grow different varieties of tomatoes. Farmers spray different fungicides and pesticides twice per week to manage different pests. The selected fields were located at S 04˚47ʹ41.7ʹʹ, E 038˚13ʹ11.8ʹʹ and S 06˚53ʹ38.3ʹʹ, E 037˚36ʹ07.4ʹʹ Random sampling using “W” Pattern was used to get representation of the fields. Occurrence of pest population was estimated from ten plants during 2018/19, searching from young, middle and older leaves. Insect specimens were collected using fine forceps, aspirators, and preserved in ethanol 70% for laboratory identification. The results showed no aphids were detected from frequent sprayed tomato fields, other pests observed include the white flies with mean (57) individuals per plant, followed by leaf miner (70) and the highest number was thrips representing (107) Mean population comparison showed a significant differences P< 0.005. Understanding occurrence of different pests in tomato growing areas could assist in planning sustainable Integrated Pest Management programme in tomato growing areas.